Artificial insemination with donor sperm (AID): heterogeneity in sperm banking facilities in a single country (Belgium) - Thijssen, A. (Universa Press, 2014)
Due to the high inflow of foreign patients seeking cross-border reproductive care in Belgium and the increased number of lesbian couples and single women who call for artificial insemination with donor sperm (AID), Belgian sperm banks nowadays face a shortage in donor sperm. However, since there is no central registration system for sperm donors in Belgium, no figures are currently available supporting this statement. Therefore a study was performed to obtain a detailed overview of the sperm banking facilities in Belgium. Questionnaires were sent to all Belgian centres for assisted reproduction with laboratory facilities (n = 18) to report on their sperm banking methods. The results showed that 82% of the centres rely partially or completely on foreign donor sperm. Moreover, four of the thirteen centres that have their own sperm bank use imported donor sperm in > 95% AID cycles. Our results show that in 63% of the Belgian AID cycles imported Danish donor sperm is being used. Donor recruitment is mainly performed through the centre’s website (61%) or by distributing flyers in the centre (46%) and 9 to 180 potential donors have been recruited per centre in 2013. Eventually, 15 to 50% of these candidate donors were accepted. Different criteria for donor acceptance are handled by the centres: donor age limits range from 18-25 to 36-46 years old, and thresholds for sperm normality differ considerably. We can conclude that a wide variation in methods associated with sperm banking is observed in Belgian centres.